The impact of the dental caries on the quality of patients' life - Editorial Article (LLC "Endo Press", 2020)
Among all oral diseases leading position holds dental caries and its complications. Despite the fact that modern dentistry has made great strides in the prevention and treatment of dental caries, the literature suggests maintaining a high prevalence of dental caries and its complications , reaching up to 98-100 % of the adult population. From our perspective, the ineffectiveness of measures for the prevention and treatment of dental caries and its complications can be connected with the individual characteristics of patients , such as their psychological state and behaviors. Based on the above, the aim of this work was to study the quality of life of patients with caries. The study involved 141 people aged 21 to 50 years, mean age was 37,2 ± 7,6 years. The study groups were identified with different levels of quality of life and made recommendations to improve the quality of life for patients with study pathology.